Perkembangan Evaluasi Tata Kelola Teknologi Informasi: Literature Review - Khansa, Shafa Salsabila; Ramadhan, Della Novia; Alfarisy, Ahmad Fadil; Fitroh, Fitroh (ICSE (Institute of Computer Sciences and Engineering), 2022)
Information technology is an important organizational asset to be managed and maximized so that its use can be aligned with business needs, thus helping to improve the achievement of the organization's vision and mission. Therefore, the implementation of information technology governance in every organization needs to be monitored for its implementation, this makes the organization more mature and immediately makes improvements to its management of its IT assets. Various studies have been conducted to evaluate IT governance in organizations using various frameworks. This study aims to conduct a review of previous studies related to the development of IT governance evaluation in reviewing research activities carried out in a certain period, analyzing the framework used and why the framework is used. The results show that research to evaluate IT governance peaked in 2014 which was dominated by the institutional sector using the COBIT 5 framework and the various reasons for using COBIT 5 are discussed further in this study.